Implementing an Internal Development Process Benchmark Using PDM-Data - Roelofsen, J.; Fuchs, S. D.; Fuchs, D. K.; Lindemann, U. (Cranfield University Press, 2009)
This paper introduces the concept for an internal development process benchmark using PDM-data. The analysis of the PDM-data at a company is used to compare development work at three different locations across Europe. The concept of a tool implemented at the company is shown as well as exemplary analyses carried out by this tool. The interpretation portfolio provided to support the interpretation of the generated charts is explained and different types of reports derived from the analyses described.
Organised by: Cranfield University
Keywords: Process Benchmark; Product Development Process